1999
DOI: 10.1001/archopht.117.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the Visual Field in the Human Occipital Cortex

Abstract: To evaluate the retinotopic map of the human occipital cortex by correlating magnetic resonance imaging (MRI) findings with visual field defects in patients with occipital lobe infarcts and to assess the compatibility between our cliniconeuroimaging findings and the location of lesions predicted by the classic Holmes map and a revised map. Methods: Magnetic resonance images were obtained in 14 patients with occipital lobe infarcts. Visual field analysis was performed with tangent screen, the Goldmann perimeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…However, recent studies pointed out an expansion of the area corresponding to central vision in the posterior part of the striate cortex [3,4,5,6]. Horton and Hoyt [5] indicated the underestimation of the cortical magnification of central vision in the Holmes' [2] map.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent studies pointed out an expansion of the area corresponding to central vision in the posterior part of the striate cortex [3,4,5,6]. Horton and Hoyt [5] indicated the underestimation of the cortical magnification of central vision in the Holmes' [2] map.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the area corresponding to the central visual field within 10° amounted to about 50% of the striate cortex, based on the correlation between the localizations of striate cortex lesions imaged by MRI and visual field defects in humans [5]. According to a study by Wong and Sharpe [4], 37% of the total surface area of the medial occipital cortex corresponded to the central 15° of vision. McFadzean et al [3] reported that the central 10° of the visual field occupied at least 50-60% of the striate cortex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations